Biodiesel production in a novel continuous flow microwave reactor. (November 2015) - Choedkiatsakul, I.; Ngaosuwan, K.; Assabumrungrat, S.; Mantegna, S.; Cravotto, G.
Abstract: This paper presents the use of a commercial FlowSynth microwave reactor for the continuous production of biodiesel from palm oil. A high ester content of 99.4% can be obtained in only 1.75 min residence time at a methanol to oil molar ratio of 12, a microwave heating power of 400 W, reaction temperature of 70 °C and NaOH catalyst loading of 1%wt of oil. The process energy consumption has also been investigated in order to assess the potential advantages of using microwave irradiation for biodiesel production. The energy consumption of palm oil transesterification as low as 0.1167 kWh/L of biodiesel was required, proving that microwave reactors need less energy consumption as compared to conventional processes. Moreover, all main biodiesel properties are in accordance with EN/ASTM standards. Graphical abstract: Highlights: High ester content of 99.4% can be obtained in a short residence time of 1.75 min. This process required an energy consumption of about a half of the conventional process. All properties of obtained biodiesel were in the range of EN/ASTM standard limit.